2017
DOI: 10.1089/jmf.2016.0077
|View full text |Cite|
|
Sign up to set email alerts
|

Capsicum annuumvar.grossum(Bell Pepper) Inhibitsβ-Secretase Activity andβ-Amyloid1–40Aggregation

Abstract: The deposition of amyloid protein as senile plaques is the major signature of Alzheimer's disease (AD). It is produced by the sequential cleavage of the amyloid precursor protein by secretases. Moreover, peppers are noted for their antiaging and cognitive enhancing properties. Thus, in this study, the effects of polyphenol-rich extracts from bell pepper on amyloid production and aggregation in vitro were investigated. Bell pepper (ripe and unripe) was extracted with methanol-1 N HCl (1:1 v/v). Thereafter, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
15
0
4
Order By: Relevance
“…Mudric et al [113] studied different cultivars and varieties of Capsicum ("Lemeška" sweet, "Lemeška" hot, "Lemeška" semi-hot and "Lakošnicka") harvested in different years. Ogunruku et al [117] analyzed the variety "Grossum" in ripe and unripe maturity stages. Materska et al [121] studied two hot pepper cultivars, "Cyklon"and "Bronowicka Ostra", and two semi hot cultivars, "Tajfun" and "Tornado", at two different maturity states.…”
Section: Quantification Of Flavonoids In Capsicummentioning
confidence: 99%
See 2 more Smart Citations
“…Mudric et al [113] studied different cultivars and varieties of Capsicum ("Lemeška" sweet, "Lemeška" hot, "Lemeška" semi-hot and "Lakošnicka") harvested in different years. Ogunruku et al [117] analyzed the variety "Grossum" in ripe and unripe maturity stages. Materska et al [121] studied two hot pepper cultivars, "Cyklon"and "Bronowicka Ostra", and two semi hot cultivars, "Tajfun" and "Tornado", at two different maturity states.…”
Section: Quantification Of Flavonoids In Capsicummentioning
confidence: 99%
“…Phenolic acids from both subfamilies are reported in C. annuum L. fruits, leaves, stems and placenta. The major hydroxybenzoic acids present in Capsicum fruits are gallic acid (maximum reported 1013.0 mg/kg fw) and vanillic acid (13.29 mg/kg fw) [111][112][113]117]. Vanillic acid is present in Capsicum stems and placenta, and p-hydroxybenzoic acid was also detected in pepper's placenta [112].…”
Section: Quantification Of Flavonoids In Capsicummentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that Capsicum annuum var. grossum could be an alternative intervention for Alzheimer's disease (AD) by inhibiting β-secretase activity and β-Amyloid 1-40 aggregation [38]. It is stated that phenolic extracts from the fruits could counteract the initial aggregation of Aβ 1-40 , as well as prevent further aggregation of preformed fibrils.…”
Section: Cabai Merah Besar (Capsicum Annuum L) and (Capsicum Annuum mentioning
confidence: 99%
“…ThT solution and phosphate-buffered saline, pH 6.6 was used as a blank. This was done at time t = 0, 24, 48, 72, and 96 hr) (Ogunruku, Oboh, Passamonti, Tramer, & Boligon, 2017).…”
Section: Thioflavin-t Assaymentioning
confidence: 99%